Empowerment assessment and influential factors among patients with type 2 diabetes - Tol, Azar (BioMed Central, 2013)
BACKGROUND: Diabetic patients need high awareness of disease prevention to adopt self-management behaviors in their daily life. Central to this activity is patients’ empowerment. Current study was conducted to assess empowerment score and its related factors among type 2 diabetic patients. METHOD: A cross-sectional study carried out over a period of nine months during 2010–2011. All patients with a diagnosis of type 2 diabetes including those referring to four hospitals affiliated with Tehran University of Medical Sciences were recruited. A total of 688 diabetic patients were identified who met the inclusion criteria and were all included in the study. Patients’ empowerment was measured by Diabetes Empowerment Scale reflecting three dimensions including managing psychosocial aspect of diabetes, assessing dissatisfaction and readiness to change and Setting and achieving diabetes goal. Collected data was analysed using SPSS software version 11.5. RESULTS: As total, 688 were available for analysis, ranging from 37–81 years old with mean of 54.41 years (SD = 8.22). The Mean duration of the disease was approximately 6.67 years (SD = 4.58). Dimensions of ‘managing the psychosocial aspect of diabetes’, ‘assessing dissatisfaction and readiness to change’ and ‘setting and achieving diabetes goal’ were all measured and scored for each patient. The mean score for each domain was 25.75 ± 5.55, 24.78 ± 7.54, 27.63 ± 7.90, respectively. Data analysis revealed a statistically significant reverse relationship between age and ‘assessing dissatisfaction and readiness to change’ and ‘setting and achieving diabetes goal’. In addition, disease duration had a statistically significant reverse relationship with ‘assessing dissatisfaction and readiness to change’. CONCLUSION: Patients with type 2 diabetes have the potential to be empowered to manage their chronic disease if they are actively informed and educated.